Status and prospects of innovative educational technologies’’ development in Ukraine - Syedov, А.О. (Journal of Information Technologies in Education (ITE), 2007)
Education as one of the most important components of society, depending on one hand on the processes happening in it, must quickly react and correspond to the state of scientific and technical progress, trends of country economic sphere development, on the other hand, it certainly influences all the processes and sides of life as it trains specialists, develops personality, forms certain life views. That is why the modern state, problems of implementation and prospects of innovative technologies in our country deserve special attention. The article is dedicated to the questions of classification and problems of implementation of innovative educational technologies.